Indigenous Peoples and the Globalization of Restorative Justice - Tauri, Juan Marcellus (Social justice, 2016)
Much of the criminological research and literature to date on the globalization of crime control has focused on macro-level theorizing about whether such globalization exists, and if so, its extent, scale, and impact. Little attention has been paid to the micro-level impact of all this activity, and in particular to the experiences of Indigenous peoples residing in settler colonial contexts. This article seeks to address this gap while also meeting Aas's exhortation that criminologists systematically explore connections between globalization and colonization. The article argues that the globalization of the restorative justice industry, especially the development of interventions such as family group conferencing, has had a profound impact on the ability of Indigenous peoples to develop and practice their own responses to social harm.